Maximizing Nonmonotone Submodular Functions under Matroid or Knapsack Constraints - Lee, Jon; Mirrokni, Vahab S.; Nagarajan, Viswanath; Sviridenko, Maxim (SIAM journal on discrete mathematics, 2010)
Submodular function maximization is a central problem in combinatorial optimization, generalizing many important problems including Max Cut in directed/undirected graphs and in hypergraphs, certain constraint satisfaction problems, maximum entropy sampling, and maximum facility location problems. Unlike submodular minimization, submodular maximization is NP-hard. In this paper, we give the first constant-factor approximation algorithm for maximizing any nonnegative submodular function subject to multiple matroid or knapsack constraints. We emphasize that our results are for nonmonotone submodular functions. In particular, for any constant $k$, we present a $(\frac{1}{k+2+\frac{1}{k}+ε})$-approximation for the submodular maximization problem under $k$ matroid constraints, and a $(\frac{1}{5}-ε)$-approximation algorithm for this problem subject to $k$ knapsack constraints ($ε>0$ is any constant). We improve the approximation guarantee of our algorithm to $\frac{1}{k+1+\frac{1}{k-1}+ε}$ for $k≥2$ partition matroid constraints. This idea also gives a $(\frac{1}{k+ε})$-approximation for maximizing a monotone submodular function subject to $k≥2$ partition matroids, which is an improvement over the previously best known guarantee of $\frac{1}{k+1}$.